Hakikat Pendidikan bagi Anak Usia Dini - Fauzi Fauzi (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2018)
Abstract: Early age is the â€œgolden ageâ€ that will determine the childâ€™s development in subsequent phases. This period should be worked as well as possible to optimize the development of the child in accordance with their potential trough educational stimulation. Children are unique individuals, distinctive, and intact. Therefore the development of early childhood holistically-integrated into the essence of education for young children. Education for young children should be able stimulate the overall the development potential inherent in every child, while education should be able to meet the basic needs of children. In addition, required an integrated program covering health care, human diet, education, mental stimulation, and psychosocial services to meet all basic needs of children. In addition required an integrated program covering health care, human diet, education, mental stimulation, and psychosocial services to meet all basic needs of children (physical, motor, language, mental/moral, emotional, and social) in order to grow and develop optimally according to its potential. Keywords: Education, Early Chilhood, and Children Development.